Effect of nicotine on the adherence and gene expression of selected oral microorganisms / Shan Gunasegar - Shan, Gunasegar (2017)
The ability of microbes to adhere on tooth surfaces coated with salivary pellicle lead to the formation of biofilm. Some environment risk factor such as smoking, poor oral hygiene and diet can contribute to the formation of plaque on tooth surface. The aim of this study was to investigate the effect of nicotine on the antimicrobial, adherence capacity, expression of adherence-associated genes and extracellular polysaccharide (EPS) and micro-colonies formation of selected oral microorganisms; Streptococcus sanguinis, Streptococcus mutans, Candida albicans and Candida parapsilosis. Growth profiles were carried out to determine the survival rate of the selected oral microbes in different concentration of nicotine (1, 2, 4 and 8 mg/ml). The relative number of viable microbial cells was estimated using viable plate count enumeration method and biofilm growth was quantified using crystal violet assay. Cell surface hydrophobicity and the cell aggregation were also studied. The regulations of selected genes associated with adherence were evaluated quantitatively and qualitatively by using real time and reserve transcription-polymerase chain reaction. In addition, the structure of EPS and biofilm maximum depth upon exposure with nicotine were analysed using confocal laser scanning microscope (CLSM). The results indicated that nicotine enhanced the growth of oral candida and bacteria in both planktonic and biofilm cells. Cell surface hydrophobicity and the expression of hyphal wall protein 1 (HWP1) and agglutinin-like sequences 3 (ALS3) of C. albicans and C. parapsilosis were found to increase in relative to the nicotine concentrations used. We also found that nicotine could increase the expression of Streptococcus sp. adherence-associated genes such as surface protein antigen (spaP), glucosyltransferase (gtfB), and glucan binding protein B (gbpB). Interestingly, the iv thickness of biofilm was increased as the nicotine concentration increases. The data concluded that nicotine can promote the growth of S. sanguinis, S. mutans, C. albicans and C. parapsilosis and influences its adherence on the plastic wells which mimic tooth surfaces. The findings of the study may have implications in improving and providing better healthcare for heavy smokers to reduce dental biofilm. In addition, the overall outcomes of this research may be applied to smoking cessation measures in smokers and aid in providing guidelines for control and preventive measures of dental biofilm associated oral diseases.